2018
DOI: 10.1021/acs.jproteome.8b00953
|View full text |Cite
|
Sign up to set email alerts
|

Smell of Infection: A Novel, Noninvasive Method for Detection of Fish Excretory-Secretory Proteins

Abstract: Chemical signals are produced by aquatic organisms following predatory attacks or perturbations such as parasitic infection. Ectoparasites feeding on fish hosts are likely to cause release of similar alarm cues into the environment due to the stress, wounding, and immune response stimulated upon infection. Alarm cues are often released in the form of proteins, antimicrobial peptides, and immunoglobulins that provide important insights into bodily function and infection status. Here we outline a noninvasive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…However, major practical challenges are associated with screening non‐liquid matrices such as plants and soil for eDNA, which include limited sample volume capacity per extraction and the presence of PCR inhibitors (Cuthill, 2020; Thomsen & Willerslev, 2015). Considering that water is the optimal screening matrix for eDNA, other molecular markers also present in water and that may be specific for distinct F. hepatica life stages, such as protein or RNA (Pawluk et al, 2018; Veilleux et al, 2021), could be targeted in future environmental water‐based surveys, although substantial research would need to be undertaken initially to characterize proteins and/or RNA markers that are specific to each F. hepatica life cycle stage (Cwiklinski & Dalton, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, major practical challenges are associated with screening non‐liquid matrices such as plants and soil for eDNA, which include limited sample volume capacity per extraction and the presence of PCR inhibitors (Cuthill, 2020; Thomsen & Willerslev, 2015). Considering that water is the optimal screening matrix for eDNA, other molecular markers also present in water and that may be specific for distinct F. hepatica life stages, such as protein or RNA (Pawluk et al, 2018; Veilleux et al, 2021), could be targeted in future environmental water‐based surveys, although substantial research would need to be undertaken initially to characterize proteins and/or RNA markers that are specific to each F. hepatica life cycle stage (Cwiklinski & Dalton, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical methods for diagnostics encompass a variety of techniques all of which utilise some form of biochemical signal to conduct the diagnosis. These techniques vary from those which detect chemical signals (volatile organic compounds, or VOCs) released during infection (e.g., Pawluk et al 100 who identified chemical cues from infected and uninfected fish), to biosensors that use biochemical reactions to detect (optical, volatile, electrochemical or mass‐sensitive) chemical compounds. When considering their application to aquatic diagnostics, the information gained from these health parameters is currently too general for diagnostics, especially in a preventative context, and the benefits would not outweigh the costs.…”
Section: Cellular Diagnosticsmentioning
confidence: 99%
“…Avoidance mechanisms are based on the remote sensing of pathogen-associated metabolites 1 that activate the olfactory and/or other chemosensory systems in the body. In fact, there is now increasing evidence from nematodes 3 and fruitflies 4 to fishes 5 , rodents 6,7 and humans 8,9 that chemosensory cues associated with harmful microbes or inflammation and reduced fitness can be detected and avoided by conspecifics. In the mouse, interest has focused on the vomeronasal organ (VNO), a chemosensory organ that provides sensory input to the accessory olfactory bulb (AOB) in the olfactory forebrain 1012 .…”
Section: Introductionmentioning
confidence: 99%